Sensory Ecology of Predator-Induced Phenotypic Plasticity - Weiss, Linda C. (Frontiers in Behavioral Neuroscience, 2019)
Ecological communities are organized in trophic levels that share manifold interactions forming complex food webs. Infochemicals can further modify these interactions, e.g. by inducing defenses in prey. The micro-crustacean Daphnia is able to respond to predator-specific chemical cues indicating an increased predation risk. Daphnia shows plastic responses by adapting its morphology, behavior and physiology, increasing organism and population fitness. This stabilizes community structures. This review will describe the progress that has been made in understanding the high degree of plasticity observed in the model crustacean Daphnia. I summarize current knowledge on the processes of predator detection, ranging from the nature of biologically active chemical cues to the underlying neurophysiological mechanisms. With this, I aim to provide a comprehensive overview on the molecular mechanisms of ad hoc environmental phenotypic adaptation. In times of climate change and pollution understanding information transfer in aquatic systems is valuable as it will allow us to predict whether and how community structures are being affected.